2018
DOI: 10.1200/jco.2017.75.9308
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Radiologic, Pathologic, and Molecular Characteristics of Long-Term Survivors of Diffuse Intrinsic Pontine Glioma (DIPG): A Collaborative Report From the International and European Society for Pediatric Oncology DIPG Registries

Abstract: Purpose Diffuse intrinsic pontine glioma (DIPG) is a brainstem malignancy with a median survival of < 1 year. The International and European Society for Pediatric Oncology DIPG Registries collaborated to compare clinical, radiologic, and histomolecular characteristics between short-term survivors (STSs) and long-term survivors (LTSs). Materials and Methods Data abstracted from registry databases included patients from North America, Australia, Germany, Austria, Switzerland, the Netherlands, Italy, France, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
281
1
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 305 publications
(322 citation statements)
references
References 33 publications
14
281
1
5
Order By: Relevance
“…A total of 35 patients (79.5%) were identified with H3F3A or HIST1H3B mutation (Figure 2). In this subgroup, the median age at diagnosis was 9 years (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), and the median overall survival was 7.9 months ( IQR 3,8;13,9). Twenty-three patients (65.7%) had a tumor exclusively located in the brainstem, whereas 8 patients (22.9%) had a tumor in another midline location, as described previously.…”
Section: Main Molecular and Chromosomal Alterationsmentioning
confidence: 95%
See 1 more Smart Citation
“…A total of 35 patients (79.5%) were identified with H3F3A or HIST1H3B mutation (Figure 2). In this subgroup, the median age at diagnosis was 9 years (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22), and the median overall survival was 7.9 months ( IQR 3,8;13,9). Twenty-three patients (65.7%) had a tumor exclusively located in the brainstem, whereas 8 patients (22.9%) had a tumor in another midline location, as described previously.…”
Section: Main Molecular and Chromosomal Alterationsmentioning
confidence: 95%
“…Due to their location, complete surgical removal is impossible. Treatment is essentially based on radiation therapy given that successive clinical trials have not identified a benefit from adjuvant or neoadjuvant chemotherapy (1,14,20). Unfortunately, radiation therapy remains palliative and only increases survival by 3-4 months (20).…”
Section: Introductionmentioning
confidence: 99%
“…Typical DIPG images have depicted it as arising from the brainstem and being diffusively involved in more than half of the pons. Surprisingly Hoffmann et al found that the MRIs of short-term survivors were associated with a low necrosis percentage but a less frequent ring enhancement [50]. All those studies might explain a balance between level of hypoxic zones, neoangiogenesis and the high diffusive phenotype of the pHGG cells side to side with normal neurons and fibers, especially in pons.…”
Section: Macroscopic and Microscopic Aspects Of Phgg Hypoxia Within Tmentioning
confidence: 98%
“…Additionally, this challenge highlights the need for international collaboration at a global scale. For instance, the joint report of the International and European Society for Pediatric Oncology DIPG Registries, which gathered comprehensively annotated information on more than 1000 cases of DIPG and the integrated molecular meta‐analysis of 1000 pHGG and DIPG constitute successful examples of large‐scale transatlantic collaborations. Translation of these joint initiatives into collaborative randomized clinical trials will be essential to conduct biomarker‐driven studies for specific subsets of pHGG.…”
Section: Future Trials In Phggmentioning
confidence: 99%